Montando o quebra-cabeça: análise de laudos elaborados por psicólogos do judiciário nos casos de abuso sexual intrafamiliar - Oshima, Elaine Beatriz Ferreira de Souza (2016)
Worldwide children and adolescents have been victims of intrafamilial sexual abuse, which is, in some cases, physically unidentifiable. In such circumstances, the victim’s account is the only available evidence to build a sexual abuse case in court. Thus, magistrates seek for expert’s support aiming the extinction, as much as possible, of eventual doubts. Granting an injunction is, therefore, of upmost importance, and while it has legal basis, it intends to protect the best interest of the child and the adolescent. This study evaluated the report provided by the judiciary psychologist in intrafamilial sexual abuse cases, where no proof of carnal knowledge was available. Hence, 20 claims with allegations of intrafamilial sexual abuse without proof of carnal knowledge were examined. Among them, 8 claims of family power dismissal and 12 protective measures, running at Children’s Court, where a Public Defender is part. These records were categorized as follows: (a) case type; (b) date of filing; (c) parties; (d) the victim's gender; (e) age of the victim; (f) alleged abuser; (g) a brief account of the facts; (h) conducting psychological report before filing; (i) the child's hearsay and adolescent psychologist by the judiciary; (j) conducting psychological report before the preliminary intervention and (m) in line decision in the report. Initially, the data was submitted to descriptive statistical analysis made through IBM SPSS, having the results to be analyzed and compared with available literature on this subject. Henceforth, IRAMUTEQ software was used to analyze the psychological reports provided by the judiciary’s technical staff. The cited software performs lexicographical, similarity and factor analysis of correspondence on the data input. Finally, the report provided by the judiciary psychologist, was considered as expert evidence, even though it can be limited to a technical transcription of the case, collected by statements from the parts involved.